Chitinase-induced resistance against Neoscytalidium dimidiatum on dragon trees: the effect of oligochitosan prepared by the heterogeneous degradation of chitosan with H2O2 under hydrothermal conditions - Du, Bui Duy; Kim Dung, Lai Thi; Dang Khoa, Vo Nguyen; Thang, Nguyen Duy; Anh Tuan, Le Nghiem (Vietnam Journal of Chemistry, 2015)
The heterogeneous degradation of chitosan with 5 % H2O2 under hydrothermal conditions (t = 75 minutes) was studied. The molecular weight of chitosan oligomer is 5 kDa. The degraded chitosan was characterized by gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FT-IR). Oligochitosan (OCT) can regulate in plant defense responses in many aspects. In this study when treated   with oligochitosan (OCT 150 ppm), the dragon trees increased the activities of chitinase resistance against Neoscytalidium dimidiatum in white spot disease. The result suggested the role of triggering a mechanism of OCT for pathogen inhibition and disease control.